2021
DOI: 10.31729/jnma.5386
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of Adverse Drug Reactions Reporting among Doctors and Nurses in a Tertiary Care Hospital: A Descriptive Cross-sectional Study

Abstract: Introduction: Doctors and nurses have a significant role in the detection of serious and unusual drug reactions. Effective implementation of an adverse drug reaction reporting system is required to ensure patient safety and quality care. This study’s objective was to find the prevalence of good knowledge of adverse drug reaction reporting among the Doctors and nurses working in a tertiary care hospital. Methods: A descriptive cross-sectional study was conducted among doctors and nurses from 15 February 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
1
1
0
Order By: Relevance
“…Unavailability of reporting form has been identified as an important factor that negatively affect ADR reporting in various studies. 15,18,28 We found that the time constraint was not a major issue while reporting ADR which was similar to Adisa 28 but inconsistent to Rashmi et al 16 Singh et al 17 ,Gupta et al 29 and Shah et al 30 The participants of our study has been reporting verbally in meeting, to the colleagues or to the pharmacy therefore time may not have been a prominent obstacle for them. However, if they knew the process of reporting .i.e.…”
Section: Table 2: Factors Influencing Decision To Report Adrsupporting
confidence: 74%
“…Unavailability of reporting form has been identified as an important factor that negatively affect ADR reporting in various studies. 15,18,28 We found that the time constraint was not a major issue while reporting ADR which was similar to Adisa 28 but inconsistent to Rashmi et al 16 Singh et al 17 ,Gupta et al 29 and Shah et al 30 The participants of our study has been reporting verbally in meeting, to the colleagues or to the pharmacy therefore time may not have been a prominent obstacle for them. However, if they knew the process of reporting .i.e.…”
Section: Table 2: Factors Influencing Decision To Report Adrsupporting
confidence: 74%
“…The incidence of ADRs which were reported in the present study was average. Indeed, there is every chance for variability in the ADRs with respect to the country and also to the various prescribing patters chosen [10].…”
Section: Discussionmentioning
confidence: 99%